Business Research Ethics Committees - Mohamed Aldarabseh, Wissal (Finance and Business Economies Review, 2019)
Developed countries use scientific research to solve their problems, promote their societies and achieve sustainable development. To organize the research activities and to ensure its integrity and credibility, research ethics committees have been established in the academic institutions of these countries. In developing countries, including the Arab world, many academic institutions lack such committees, especially in humanitarian colleges. This study highlights the importance of the ethics committees of scientific research in Business faculties. In addition, the structure, duties and procedures utilized by such committees were also covered. As an introduction to the topic, the basic concepts of research ethics were also reviewed